ASEAN Single Market: Revisiting Rules and Strategies on the Enforcement of Free Flow of Goods in ASEAN - Anwar, Riyad Febrian (Hasanuddin Law Review, 2015)
Whether we are ready or not, people in Indonesia and the rest of Southeastern Asia will soon welcome the ASEAN Economic Communities (AEC) by the end 2015. Therefore, there are needs to evaluate the progress in ASEAN rules and strategies thus far. By employing normative study, this paper finds and further recommends the following: Firstly, ASEAN almost reached its peak points in eliminating the tariff barriers, yet to come are the elimination on ‘sensitive’ and ‘highly sensitive list’ tariffs on imported agriculture commodities; Secondly, Non-Tariff Barriers (NTB) remain to be one of the major problems in intra-ASEAN trades; Thirdly, Member States reluctances to invoke the ASEAN dispute settlement mechanism for their trading disputes may potentially hinder the effectiveness of AEC in the future; and Finally, the protection of intellectual property remains low in the region as the ASEAN Intellectual Property Rights (IPR) Action plan 2011-2015 is still deemed ineffective to reforms the IP regulations within Member States.